2007
DOI: 10.1007/s11205-007-9214-3
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Role of ICTs in Quality of Life in Three Chinese Cities

Abstract: QoL in Chinese societies, ICTs role in QoL, Quality of life, ICT-QoL needs, Internet and QoL,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This reinforces Internet users' profound belief, regardless of race, gender, and culture, in the fundamental right to the free flow of information and the importance of evaluating and judging if information is accurate and trustworthy. As expected, Internet users competent with Internet tools such as keyboarding, basic programming, knowledge and use of appropriate connectivity methods, networking, data bases, desktop publishing, and communication hardware and software tended to be knowledgeable in accessing the information necessary for making important life decisions (Lee et al 2008;Murray 2003). These decisions may include getting information on school, university, or career training; helping to find or move work; getting information on a cure or treatment to deal with a major illness or health condition; making a major investment or financial decision; finding a way to save or to make money; and developing lasting interpersonal relationships and/or finding romance.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…This reinforces Internet users' profound belief, regardless of race, gender, and culture, in the fundamental right to the free flow of information and the importance of evaluating and judging if information is accurate and trustworthy. As expected, Internet users competent with Internet tools such as keyboarding, basic programming, knowledge and use of appropriate connectivity methods, networking, data bases, desktop publishing, and communication hardware and software tended to be knowledgeable in accessing the information necessary for making important life decisions (Lee et al 2008;Murray 2003). These decisions may include getting information on school, university, or career training; helping to find or move work; getting information on a cure or treatment to deal with a major illness or health condition; making a major investment or financial decision; finding a way to save or to make money; and developing lasting interpersonal relationships and/or finding romance.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…On the one hand, some findings indicate that Internet adoption is associated with increased subjective well-being (McKenna and Bargh, 2000;DiMaggio et al, 2004;Elgar et al, 2011). A number of studies have revealed a positive association between online activities and perceived quality of life in Asian countries (Lee et al, 2008;Oh, Ozkaya, and LaRose, 2014;Lissitsa and Chachashvili-Bolotin, 2016). Moreover, scholars have attempted to explain the mechanisms through which Internet use may improve subjective well-being.…”
Section: The Social Implications Of Internet Adoptionmentioning
confidence: 99%
“…Wei and Gao, 2017) or neglect the rural-urban divide in urban China (e.g. Lee et al, 2008). Second, and perhaps more importantly, most previous work in this field has been based on cross-sectional data, which does not allow researchers to explore the potential impact of the dynamics of online activities on well-being across different time periods.…”
Section: Research Questionsmentioning
confidence: 99%
“…Concerns over global environmental issues, particularly on saving trees, have also seen an increased awareness where most people have resorted to the e-system such as enewspaper, e-banking, e-government and emails in managing their day-to-day routines. Consequently, a study on the effectiveness of electronic media has been carried out to evaluate their impact on quality of life (Lee, Leung, Lo & Xiong, 2008;Lee, Leung, Lo, Xiong & Wu, 2011;Robinson and Martin, 2009;Liang, 2011;Chan & Huang, 2004;Boase, Horrigan, Wellman & Rainie, 2006). In this respect, the Internet and mobile phones have been found to be the two most important media in raising people's quality of life compared to television and other electronic media (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a study on the effectiveness of electronic media has been carried out to evaluate their impact on quality of life (Lee, Leung, Lo & Xiong, 2008;Lee, Leung, Lo, Xiong & Wu, 2011;Robinson and Martin, 2009;Liang, 2011;Chan & Huang, 2004;Boase, Horrigan, Wellman & Rainie, 2006). In this respect, the Internet and mobile phones have been found to be the two most important media in raising people's quality of life compared to television and other electronic media (Lee et al, 2008). However, Robinson and Martin (2009) claim that the Internet has resulted in fewer social visits by relatives and neighbours but higher visits by friends.…”
Section: Introductionmentioning
confidence: 99%